2014
DOI: 10.1210/me.2014-1047
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Receptor Enhances Kidney Stone-CaOx Crystal Formation via Modulation of Oxalate Biosynthesis & Oxidative Stress

Abstract: Males develop kidney stones far more frequently than females with a ratio of 2–3:1, suggesting that androgen receptor (AR) signaling might play a key role in the development of nephrolithiasis. Using the cre-loxP system to selectively knock out AR in glyoxylate-induced calcium oxalate (CaOx) crystal mouse models, we found that the mice lacking hepatic AR had less oxalate biosynthesis, which might lead to lower CaOx crystal formation, and that the mice lacking kidney proximal or distal epithelial AR also had lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 65 publications
1
56
0
1
Order By: Relevance
“…Androgen leads to the accumulation of some damaging factors for kidney stone formation, such as calcium, oxalate, and uric acid in urine. 22,23 Men are also more likely to engage in heavy physical labour, to sweat more, and more often be dehydrated. These factors are documented risk factors for kidney stone formation.…”
Section: Discussionmentioning
confidence: 99%
“…Androgen leads to the accumulation of some damaging factors for kidney stone formation, such as calcium, oxalate, and uric acid in urine. 22,23 Men are also more likely to engage in heavy physical labour, to sweat more, and more often be dehydrated. These factors are documented risk factors for kidney stone formation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in rats suggest that testosterone increases and estrogen decreases urinary oxalate excretion(21). A recent study in mice that lack the hepatic androgen receptor (AR) documented reduced oxalate biosynthesis (22), and that mice lacking kidney proximal or distal epithelial AR also had lower CaOx crystal formation. Other in vivo studies found that collagen synthesis was inhibited by estrogen but not affected by testosterone (23).…”
Section: Discussionmentioning
confidence: 99%
“…CaOx not only obstructs ureters, but also induces reactive oxygen species (ROS), which results in renal cellular injury and inflammation [8,9]. Liang et al have reported that androgen receptor degradation enhancer, ASC-J9, inhibits the formation of CaOx crystals by regulating oxalate biosynthesis and oxidative stress both in vivo and in vitro [10]. In addition, erythrocyte oxidative damage contributes to the tubular damage and stone formation [11].…”
Section: ------------------------------------------------------------mentioning
confidence: 99%